Impaired NF-κB signalling underlies cyclophilin D-mediated mitochondrial permeability transition pore opening in doxorubicin cardiomyopathy. Issue 6 (6th September 2019) - Dhingra, Rimpy; Guberman, Matthew; Rabinovich-Nikitin, Inna; Gerstein, Jonathon; Margulets, Victoria; Gang, Hongying; Madden, Nicholas; Thliveris, James; Kirshenbaum, Lorrie A
Abstract: Aims: The chemotherapy drug doxorubicin (Dox) is commonly used for treating a variety of human cancers; however, it is highly cardiotoxic and induces heart failure. We previously reported that the Bcl-2 mitochondrial death protein Bcl-2/19kDa interaction protein 3 (Bnip3), is critical for provoking mitochondrial perturbations and necrotic cell death in response to Dox; however, the underlying mechanisms had not been elucidated. Herein, we investigated mechanism that drives Bnip3 gene activation and downstream effectors of Bnip3-mediated mitochondrial perturbations and cell death in cardiac myocytes treated with Dox. Methods and results: Nuclear factor-κB (NF-κB) signalling, which transcriptionally silences Bnip3 activation under basal states in cardiac myocytes was dramatically reduced following Dox treatment. This was accompanied by Bnip3 gene activation, mitochondrial injury including calcium influx, permeability transition pore (mPTP) opening, loss of nuclear high mobility group protein 1, reactive oxygen species production, and cell death. Interestingly, impaired NF-κB signalling in cells treated with Dox was accompanied by protein complexes between Bnip3 and cyclophilin D (CypD). Notably, Bnip3-mediated mPTP opening was suppressed by inhibition of CypD—demonstrating that CypD functionally operates downstream of Bnip3. Moreover, restoring IKKβ–NF-κB activity in cardiac myocytes treated with Dox suppressed Bnip3 expression, mitochondrial perturbations, and necrotic cell death. Conclusions: The findings of the present study reveal a novel signalling pathway that functionally couples NF-κB and Dox cardiomyopathy to a mechanism that is mutually dependent upon and obligatorily linked to the transcriptional control of Bnip3. Our findings further demonstrate that mitochondrial injury and necrotic cell death induced by Bnip3 is contingent upon CypD. Hence, maintaining NF-κB signalling may prove beneficial in reducing mitochondrial dysfunction and heart failure in cancer patients undergoing Dox chemotherapy. Graphical Abstract: